2018
DOI: 10.1159/000490853
|View full text |Cite
|
Sign up to set email alerts
|

The Community Pharmacist’s Role in Reducing Cardiovascular Risk Factors in Lebanon: A Longitudinal Study

Abstract: Objective: To assess the role of the pharmacist in modifying risk factors for cardiovascular disease (CVD) among Lebanese adults in urban and rural areas. Methods: In a prospective survey, 865 out of 1,000 participants aged ≥45 years, previously interviewed, agreed to be followed at 1 and 2 years time points. Parameters including blood pressure, lipid profile, blood glucose, average number of risk factors, and atherosclerotic CVD (ASCVD) risk were assessed and evaluated at the beginning of the study, then aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
(30 reference statements)
2
5
0
Order By: Relevance
“…This result builds on existing evidence of preventive strategies against CVDs which should be done at the primary health promotion level before a person, or the population becomes afflicted with some of the causes of CVD 30 . Again, a study in Lebanon affirms the observation that including pharmacists in CVD prevention plan can improve CVD prevention by decreasing the risk factors 41 . With the involvement of community pharmacists in CVD preventive activities, the risk factors of CVD including hypertension, diabetes, smoking, physical inactivity, and hypercholesterolemia can be prevented by constantly monitoring and educating clients on these risk factors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This result builds on existing evidence of preventive strategies against CVDs which should be done at the primary health promotion level before a person, or the population becomes afflicted with some of the causes of CVD 30 . Again, a study in Lebanon affirms the observation that including pharmacists in CVD prevention plan can improve CVD prevention by decreasing the risk factors 41 . With the involvement of community pharmacists in CVD preventive activities, the risk factors of CVD including hypertension, diabetes, smoking, physical inactivity, and hypercholesterolemia can be prevented by constantly monitoring and educating clients on these risk factors.…”
Section: Discussionmentioning
confidence: 87%
“…30 Again, a study in Lebanon affirms the observation that including pharmacists in CVD prevention plan can improve CVD prevention by decreasing the risk factors. 41 With the involvement of community pharmacists in CVD preventive activities, the risk factors of CVD including hypertension, diabetes, smoking, physical inactivity, and hypercholesterolemia can be prevented by constantly monitoring and educating clients on these risk factors.…”
Section: Community Pharmacists′ Role In the Prevention Of Cardiovascu...mentioning
confidence: 99%
“…This review has identified a variety of statistical analysis methods that have been incorporated to analyze time-to-event and longitudinal outcome data. Three (3.8%) used a simple statistical test [ 14 16 ]. For example, Albani et al [ 16 ] used the Wilcoxon signed rank test to compare two risk scores (the Framingham Risk Score and an atherosclerotic cardiovascular disease risk score) before treatment with pasireotide and 6 and 12 months after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacists shall be actively involved in many programs, including monitoring CVD risk factors, optimizing medications, diseases and health care wellness, public health, educational consultations, and preventive care ( Alshahrani et al, 2020 , Newman et al, 2020 , Vigneshwaran et al, 2013 ). Much research has established pharmacists' involvement in preventing and controlling CVD ( Alavudeen et al, 2023 , Almansour et al, 2021 , Fahs et al, 2018 , Peletidi et al, 2019 ). A recent report confirmed that practicing community pharmacists in Saudi Arabia have considerable knowledge and understanding of CVD risk factors ( Sulaiteen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%